The Mechanism of Citrus Host Defense Response Repression at Early Stages of Infection by Feeding of Diaphorina citri Transmitting Candidatus Liberibacter asiaticus - Wei, Xu; Mira, Amany; Yu, Qibin; Gmitter, Fred G. (Frontiers in Plant Science, 2021)
Citrus Huanglongbing (HLB) is the most devastating disease of citrus presumably caused by ‘Candidatus Liberibacter asiaticus’ (CaLas). Although transcriptomic profiling of HLB-affected citrus plants has been studied extensively, the initial steps in pathogenesis have not been fully understood. In this study, RNA-seq was used to compare very early transcriptional changes in Valencia sweet orange (VAL) response to CaLas after feeding by the vector Diaphorina citri (Asian citrus psyllid, or ACP). The results suggest the existence of a delayed defense reaction against the infective vector in VAL, while the attack by the healthy vector prompted immediate and substantial transcriptomic changes that led to the rapid erection of active defenses. Moreover, in the presence of CaLas-infected psyllids, several downregulated differentially expressed genes (DEGs) were identified on the signaling-, transcription factor-, hormone-, defense-, and photosynthesis-related pathways at 1 dpi (day post infestation). Surprisingly, a burst of DEGs (6,055) was detected at 5 dpi, including both upregulated and downregulated DEGs on the defense-related and secondary metabolic pathways, and severely downregulated DEGs on the photosynthesis-related pathways. Very interestingly, a significant number of those downregulated DEGs required ATP binding for activation or phosphate as substrate; meanwhile, abundant highly upregulated DEGs were detected on the ATP biosynthetic and glycolytic pathways. These findings highlight the energy requirement of CaLas virulence processes. The emerging picture is that CaLas not only employs virulence strategies to subvert the host cell immunity, but the fast-replicating CaLas might actively rewire host cellular metabolic pathways to obtain the necessary energy and molecular building blocks to support virulence and the replication process. Taken together, the very early response of citrus to the CaLas vectored by infective ACP was evaluated for the first time, thus allowing the changes in gene expression relating to the primary mechanisms of susceptibility and host-pathogen interactions to be studied, and without the secondary effects caused by the development of complex whole plant symptoms.